Applications, challenges and prospects of bionic nose in rapid perception of volatile organic compounds of food. (30th July 2023) - Xing, Zheng; Zogona, Daniel; Wu, Ting; Pan, Siyi; Xu, Xiaoyun
Graphical abstract: Highlights: Recent bionic nose applications for food detection are reviewed. Broad-spectrum electrical conductivity sensors face challenges at room temperature. Colourimetric bionic nose features both disposability and portability. Mass Transducers bionic nose provides nondestructive but lacks portability. Challenges and prospects coexist for bionic nose. Abstract: Bionic nose, a technology that mimics the human olfactory system, has been widely used to assess food quality due to their high sensitivity, low cost, portability and simplicity. This review briefly describes that bionic noses with multiple transduction mechanisms are developed based on gas molecules' physical properties: electrical conductivity, visible optical absorption, and mass sensing. To enhance their superior sensing performance and meet the growing demand for applications, a range of strategies have been developed, such as peripheral substitutions, molecular backbones, and ligand metals that can finely tune the properties of sensitive materials. In addition, challenges and prospects coexist are covered. Cross-selective receptors of bionic nose will help and guide the selection of the best array for a particular application scenario. It provides an odour-based monitoring tool for rapid, reliable and online assessment of food safety and quality.